Evektitivitas Undang-Undang Nomor 22 Tahun 2009 Pasal 273 Terhadap Kecelakaan Lalu Lintas: Studi Kasus Di Polrestabes Palembang - Dian Puspa Iwari; Evy Febryani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Law enforcement is closely related to society, in terms of success or failure. Law enforcement is also said to be effective if all components of the legal system function well. In this research the athor discuses the effectiveness of arti cle 273 of Law NO 22 of 2009 on traffic accidents and also the obstacle factors. From the number of accidents, it can be saids that Article 273 is not yet effective because the graph of the decline in the number of accidents has not fallen drastically. This is cool, there are several factor, includings: the irrelevance of the condition of existing facilities and facilities in traffic life and the public lack of undestanding of the law.